Evaluating HiPhorius Phytase in Two Diet Formulation Strategies on Finishing Pig Growth Performance, Serum Chemistry, Bone Mineralization, and Carcass Characteristics - Macie E. Reeb; Jason C. Woodworth; Joel M. DeRouchey; Mike D. Tokach; Robert D. Goodband; Jordan T. Gebhardt; Jon R. Bergstrom (Kansas Agricultural Experiment Station Research Reports, 2023)
Two experiments were conducted to determine the effects of HiPhorius (DSM Nutritional Products, Parsippany, NJ) phytase on finishing pig growth performance, serum chemistry, bone mineralization, and carcass characteristics. In Exp. 1, 1,161 pigs (PIC 337 × 1050; initially 80.9. ± 1.06 lb) were used in a 105-d trial. There were 27 pigs per pen and 10 or 11 replications per treatment. Treatments consisted of: 1) Control diet with no added phytase and formulated to NRC (2012) requirement estimates for standard total tract digestible (STTD) P; 2) 600 FYT/kg added phytase formulated to the same STTD P as the control diet considering a release of 0.13% STTD P and 0.095% STTD Ca; 3) 1,000 FYT/kg added phytase formulated to the same STTD P as the control diet considering release of 0.16% STTD P and 0.107% STTD Ca; and 4) high STTD P (no phytase; approximately 22% above NRC requirement estimates). All diets were formulated to a 1.30:1 STTD Ca:STTD P ratio. Overall, pigs fed NRC (2012) or high STTD P had increased ADG (P<0.05) compared to pigs fed the treatments with added phytase. Pigs fed diets with phytase tended to have decreased (P= 0.056) 25-hydroxyvitamin-D3compared to pigs fed NRC levels of STTD P without phytase. In Exp. 2, 1,160 pigs (PIC 337 × 1050; initially 167.4 ± 2.92 lb) were used in a 58-d trial. There were 27 pigs per pen and 11 replications per treatment. Treatments were the same as in Exp. 1, except diets were formulated to the same total Ca:P ratio (the phase 1 ratio was 1.15:1; the phase 2 ratio was 1.12:1) without an STTD Ca release consideration from phytase. Overall, there were no differences in ADG, ADFI, or F/G among treatments (P>0.10). For pigs fed NRC or high STTD P, there was an increase (P<0.05) in metacarpal bone density, and a tendency for increased bone ash weight (g) (P<0.10) and percentage bone ash (P<0.10) compared to pigs fed treatments containing phytase. In conclusion, regardless of diet formulation strategy, pigs fed diets with phytase had decreased growth performance (Exp. 1) and bone mineralization (Exp. 2). The unexpected result may be caused by several, or a combination of, factors, such as low or no monocalcium phosphate being included in the diets with phytase, lower analyzed than formulated P (based on sampled diets), not enough phytate-bound P in the diets for phytase to provide sufficient P, too wide of an analyzed Ca:P ratio that may have reduced phytase activity compared to the intended Ca:P ratio, or the expected P attributed to the phytase being overestimated.
Keywords: Ca:P ratio; finishing pig; phytase; growth performance